2019
DOI: 10.3906/bot-1803-36
|View full text |Cite
|
Sign up to set email alerts
|

Exogenous trehalose alleviates the adverse effects of salinity stress in wheat

Abstract: RETRACTED: Exogenous trehalose alleviates the adverse effects of salinity stress in wheat As stated in our publication policy, the Editors-in-Chief of the journals have the right to return or retract articles even if articles have been accepted or published in order to increase the authenticity and reliability and to prevent ethical breaches. In this respect, it has been found that this article has been published in another journal. Ensuring that the studies published in our journals are conducted in a fair an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(1 citation statement)
references
References 30 publications
0
1
0
Order By: Relevance
“…Transcriptomic and proteomic approaches have found that trehalose application upregulates Rubisco and chloroplast FBPase in wheat, even under non-stressed conditions [36,37]. In this work, the three lines transformed with the ScTPS1-TPS2 gene had higher Rubisco activity during drought stress than non-transformed wheat plants (Figure 4a), implying that increased trehalose synthesis in wheat promotes better photosynthesis because it helps maintain an efficient CO 2 fixation under drought conditions.…”
Section: Discussionmentioning
confidence: 57%
“…Transcriptomic and proteomic approaches have found that trehalose application upregulates Rubisco and chloroplast FBPase in wheat, even under non-stressed conditions [36,37]. In this work, the three lines transformed with the ScTPS1-TPS2 gene had higher Rubisco activity during drought stress than non-transformed wheat plants (Figure 4a), implying that increased trehalose synthesis in wheat promotes better photosynthesis because it helps maintain an efficient CO 2 fixation under drought conditions.…”
Section: Discussionmentioning
confidence: 57%